Strategi pengendalian pencemaran lingkungan oleh air limbah hotel di Pekanbaru - Rifati Hanifa; Thamrin Thamrin; Rahman Karnila (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2022)
According to DLHK Pekanbaru 2021 Report, hotel wastewater makes a significant contribution to environmental problems in Pekanbaru. Many hotels don’t have an IPAL permit and don't report the results of the wastewater quality test to DLHK. This will have an impact on the environment in the community. This study aims to examine the strategy of controlling environmental pollution by hotel wastewater in Pekanbaru. The research method is in the form of surveys, interviews and questionnaires to determine the quality of processing and control strategies for environmental pollution that can be caused. Used descriptive analysis and SWOT analysis. The results of this study: there are hotel BOD and COD values ​​that do not meet the quality standards of Minister of Environment Regulation No. 5 of 2014 due to the influence of visitors and the rainy season, but the values ​​of TSS, pH, ammonia, oils and fats, and total coliform have met the quality standards. There needs to be an evaluation related to hotel wastewater treatment, improvement of policies related to hotel wastewater treatment in accordance with applicable quality standards, sanctions for hotels that are negligent and do not comply with the rules, socialization to the public to care about the environment.